2014
DOI: 10.1371/journal.pone.0086182
|View full text |Cite
|
Sign up to set email alerts
|

bHLH003, bHLH013 and bHLH017 Are New Targets of JAZ Repressors Negatively Regulating JA Responses

Abstract: Cell reprogramming in response to jasmonates requires a tight control of transcription that is achieved by the activity of JA-related transcription factors (TFs). Among them, MYC2, MYC3 and MYC4 have been described as activators of JA responses. Here we characterized the function of bHLH003, bHLH013 and bHLH017 that conform a phylogenetic clade closely related to MYC2, MYC3 and MYC4. We found that these bHLHs form homo- and heterodimers and also interact with JAZ repressors in vitro and in vivo. Phenotypic ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 62 publications
6
87
0
Order By: Relevance
“…Notably, we detected the interaction of JAZ12 only with MYC2, MYC3, and MYC4, both in cell cultures and in seedlings, although many other transcription factors have been reported to interact with the JAZ proteins, including JAZ12 (Pauwels and Goossens, 2011;Hu et al, 2013;Nakata et al, 2013;SasakiSekimoto et al, 2013;Song et al, 2013;Fonseca et al, 2014). Similarly, JAZ12 is the only JAZ for which we observed interaction using COI1 as bait.…”
Section: Use Of Tap-mass Spectrometry To Study Ubiquitin E3 Ligasessupporting
confidence: 48%
See 1 more Smart Citation
“…Notably, we detected the interaction of JAZ12 only with MYC2, MYC3, and MYC4, both in cell cultures and in seedlings, although many other transcription factors have been reported to interact with the JAZ proteins, including JAZ12 (Pauwels and Goossens, 2011;Hu et al, 2013;Nakata et al, 2013;SasakiSekimoto et al, 2013;Song et al, 2013;Fonseca et al, 2014). Similarly, JAZ12 is the only JAZ for which we observed interaction using COI1 as bait.…”
Section: Use Of Tap-mass Spectrometry To Study Ubiquitin E3 Ligasessupporting
confidence: 48%
“…JAZ proteins function as repressors of specific transcription factors in the absence of JA-Ile (Niu et al, 2011;Pauwels and Goossens, 2011;Zhu et al, 2011;Hu et al, 2013;Nakata et al, 2013; Sasaki-Sekimoto et al, 2013; Song et al, 2013;Fonseca et al, 2014). The perception of jasmonates (JAs) thus leads to the derepression of these transcription factors, followed by a rapid reprogramming of gene expression (Pauwels et al, 2008;Attaran et al, 2014).…”
mentioning
confidence: 99%
“…bHLH3, bHLH13, bLHL14, and bHLH17 are repressors that bind to cis-regulatory elements of MYC target genes and inhibit transcription (Fonseca et al, 2014;Song et al, 2013;Sasaki-Sekimoto et al, 2013). We tested whether these factors could participate in the suppression of JA responses mediated by egginduced SA.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the bHLH-mediated release of MYBs from inhibition will be followed by the MYB-mediated activation of GSL biosynthesis genes. Interestingly, several independent research groups have recently demonstrated that the bHLH subgroup IIId TFs (bHLH03, bHLH13, bHLH14, and bHLH17) are targets of JAZ proteins and therefore inhibitors of JA signaling, which can indeed serve as antagonists of the bHLH subgroup IIIe (bHLH04, bHLH05, and bHLH06) analyzed in this study (Nakata et al, 2013;Sasaki-Sekimoto et al, 2013;Song et al, 2013;Fonseca et al, 2014). Furthermore, these bHLH subgroup IIId TFs function redundantly to negatively regulate JA-mediated plant defense; therefore, it is highly probable that bHLH03, bHLH13, bHLH14, and bHLH17 factors are transcriptional repressors of GSL biosynthesis and antagonize bHLH04, bHLH05, and bHLH06.…”
Section: Combinatorial Gene Regulation By Myb-bhlh Complexesmentioning
confidence: 79%